Mortality in intensive care unit in Pinar del Rio province hospital - Amanda Lucia Azcuy Castro; Rafael Miranda Pedroso (Universidad Médica Pinareña, 2019)
Introduction: intrahospital mortality rate is an important parameter in the analysis of health care and it is one of the elements that are usually taken into account when assessing the quality of a health care service or of an institution.